A new fossil Malthodes Kiesenwetter, 1852 from the Eocene Baltic amber (Coleoptera Cantharidae) - Parisi, Francesco; Fanti, Fabrizio (Zootaxa, 2019)
A new Malthodes embedded in an amber piece of the Eocene from Kaliningrad region (Russia) is illustrated and described here. Most of the species of this genus, both living and fossil, show short elytra leaving some abdominal segments uncovered, as in the case of Malthodes tognettii sp. nov. The new species is characterized by the absence of the yellow spots on the elytral apex, the last sternite strongly curved and folded backward with weakly forked apex, and by the last tergite elongate, weakly forked apically and slightly bent downwards from half-length. A key of the Malthodes embedded in Baltic amber is also provided.